A Recent Bibliometric Analysis of Nursing Service Quality: Research Growth and Key Findings - Fadhal, Muchtarul; Dioso, Regidor III (Sahabat Publikasi Kuu, 2025)
Introduction, Nursing quality is a crucial aspect of healthcare that affects patient safety, satisfaction, and overall service efficiency. This study employs a bibliometric approach to analyze global research trends on nursing quality, identifying influential authors, institutions, and key thematic developments in the field. Methods, This study conducted a bibliometric analysis using research articles indexed in Scopus. Data collection was performed using specific keywords related to nursing quality, with defined inclusion and exclusion criteria to ensure the relevance of the selected publications. The analysis focused on identifying research productivity by year, leading authors, citation impact, country contributions, and thematic trends. Results, The bibliometric analysis identified seven key findings: (1) an increasing trend in nursing quality research over the past two decades, (2) dominant contributions from the United States, the United Kingdom, and Australia, (3) highly cited articles primarily focusing on patient safety, evidence-based practice, and nursing competence, (4) leading journals such as Journal of Nursing Management and International Journal of Nursing Studies, (5) major institutional contributions from universities in North America and Europe, (6) key funding sources supporting research development, and (7) gaps in research output between developed and developing countries. The thematic analysis identified several key themes in nursing quality research, including patient safety and risk management, evidence-based nursing practices, quality improvement in healthcare institutions, professional competency development, nursing leadership and management, and policy implications for nursing standards. These themes reflect the evolving priorities and challenges in improving nursing quality worldwide. Discussion,The results indicate that research on nursing quality continues to expand, emphasizing patient-centered care, technological advancements, and evidence-based interventions. However, disparities persist in research output and collaboration between high-income and low-income countries. Strengthening global cooperation and enhancing accessibility to research resources is essential for advancing nursing quality on a broader scale.